Pengalaman Ibu dengan Bayi Berat Badan Lahir Rendah dalam Melakukan Perawatan Metode Kanguru di Rumah - Ana Rizana; Lusiana Lusiana (MAHESA : Malahayati Health Student Journal, 2026)
ABSTRACT Low birth weight (LBW) babies are babies whose weight is less than 2500 grams regardless of gestational age. Kangaroo Method Care (PMK) is an important intervention for LBW babies that involves skin-to-skin contact between mother and baby. This method aims to increase the baby's body temperature, provide a sense of security, and support the baby's physical and emotional development. LBW in carrying out PMK at home, as well as understanding the challenges and benefits experienced in carrying out PMK at home. This research used a qualitative phenomenological approach involving three mothers as participants selected through purposive sampling techniques. Data was collected through in-depth interviews which were recorded and transcribed, then analyzed using the Colaizzi method.From the data analysis, seven main the mes emerged, namely: Reasons for carrying out KMC: The mother's motivation to carry out KMC and the hope for her child's health makes the mother continue to carry out KMC. Time for implementing KMC: The duration and frequency of implementing KMC depends on the condition and abilities of the mother and baby.  Benefit of KMC: The mother feels a positive emotional response and calm during KMC. Social Support and Health Workers: Support from family, social groups and health workers plays a very important role in implementing KMC. Challenges and obstacles in implementation: Mother's anxiety level is the main obstacle factor in carrying out PMK at home. Mother's level of knowledge about PMK: In implementing PMK at home, mothers have different levels of knowledge and understanding about PMK, Solutions and strategies for facing obstacles: Motivation from within is the solution in facing obstacles. This research requires support from health workers and the social environment to increase mothers' knowledge, abilities and motivation about the importance of FMD for LBW babies. The results of the research provide recommendations for developing educational programs for mothers who have LBW babies, as well as the need for more attention to the psychological condition of mothers during care at home. It is hoped that this research can serve as a guide for further research and improve the quality of care for LBW babies in the community. Keywords: LBW, KMC, Babies.  ABSTRAK Bayi berat badan lahir rendah (BBLR) adalah bayi yang berat badannya kurang dari 2500 gram tanpa memandang usia gestasi. Perawatan Metode Kanguru (PMK) merupakan intervensi penting bagi bayi BBLR yang melibatkan kontak kulit antara ibu dan bayi. Metode ini bertujuan untuk meningkatkan suhu tubuh bayi, memberikan rasa aman, dan mendukung perkembangan fisik serta emosional bayi. Penelitian ini bertujuan untuk menggali pengalaman ibu dengan bayi BBLR dalam melaksanakan PMK di rumah, serta memahami tantangan dan manfaat yang di alami dalam melakukan PMK di rumah. Penelitian ini menggunakan pendekatan kualitatif fenomenologi dengan melibatkan tiga ibu sebagai partisipan yang dipilih melalui teknik purposive sampling. Data dikumpulkan melalui wawancara mendalam yang direkam dan ditranskrip, kemudian dianalisis menggunakan metode Colaizzi. Dari analisis data, muncul tujuh tema utama, yaitu: Alasan Melakukan PMK : Motivasi ibu untuk melakukan PMK dan harapan untukkesehatan anaknya menjadikan ibu tetap melakukan PMK, Waktu Pelaksanaan PMK : Durasi dan frekuensi pelaksanaan PMK tergantung dari kondisi dan kemampuan ibu dan bayi, Manfaat PMK: Ibu merasakan respon emosi yang positif dan ketenangan saat PMK, Dukungan Sosial dan Tenaga Kesehatan: Dukungan dari keluarga, kelompok sosial dan tenaga kesehatan sangat berperan dalam pelaksanaan PMK. Tantangan dan hambatan dalam Pelaksanaan : Tingkat kecemasan ibu menjadi faktor hambatn utama dalam melakukan PMK di rumah, Tingkat Pengetahuan Ibu tentang PMK : Dalam pelaksaan PMK di rumah, ibu memiliki tingkat pengetahuan dan pemahaman yang berbeda tentang PMK, Solusi dan strategi Menghadapi Hambatan : Motivasi dari dalam diri menjadi solusi dalam menghadapi hambatan. Penelitian ini membutuhkan dukungan dari tenaga kesehatan dan lingkungan sosial untuk meningkatkan pengetahuan, kemampuan dan motivasi ibu tentang pentingnya PMK bagi bayi BBLR. Hasil penelitian memberikan rekomendasi untuk pengembangan program edukasi bagi ibu yang memiliki bayi BBLR, serta perlunya perhatian lebih terhadap kondisi psikologis ibu selama perawatan di rumah.Penelitian ini diharapkan dapat menjadi panduan bagi penelitian selanjutnya dan meningkatkan kualitas perawatan bagi bayi BBLR di masyarakat. Kata Kunci: BBLR, PMK, Bayi.